2018
DOI: 10.1186/s13620-018-0131-3
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of three treatment protocols using oral prednisone and oral meloxicam for therapy of canine idiopathic lymphoplasmacytic rhinitis: a pilot study

Abstract: BackgroundIdiopathic lymphoplasmacytic rhinitis (LPR) is a common inflammatory disorder of the nasal cavity in dogs due to unknown etiology. It is characterised by non-specific clinical signs, including nasal discharge, epistaxis and breathing problems. Diagnosis is usually based on the histopathologic identification of infiltrating plasmocytes and lymphocytes in the nasal mucosa and the exclusion of other underlying diseases. Treatment strategies include glucocorticoids, non-steroidal anti-inflammatory drugs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
(121 reference statements)
0
10
0
Order By: Relevance
“…Due to their broad and dose-dependent biological effects, from physiologic replacement to anti-inflammatory and immunosuppression, glucocorticoids represent one of the most commonly prescribed classes of medication in veterinary medicine (1,2). In fact, according to a survey of three veterinary practices in the UK, 14.5% (2,913/20,019) of canine consults result in the use of systemic glucocorticoid therapy (3), including various indications such as atopic dermatitis (4), idiopathic lymphoplasmacytic rhinitis (5), and immune-mediated thrombocytopenia (6). However, the clinical benefits of corticotherapy are often accompanied by significant limitations such as variability in therapeutic response to labeled dosage and concerns for systemic toxicity; for instance, systemic adverse effects were reported in 10-81% of dogs receiving oral corticosteroids for the treatment of atopic dermatitis (4).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their broad and dose-dependent biological effects, from physiologic replacement to anti-inflammatory and immunosuppression, glucocorticoids represent one of the most commonly prescribed classes of medication in veterinary medicine (1,2). In fact, according to a survey of three veterinary practices in the UK, 14.5% (2,913/20,019) of canine consults result in the use of systemic glucocorticoid therapy (3), including various indications such as atopic dermatitis (4), idiopathic lymphoplasmacytic rhinitis (5), and immune-mediated thrombocytopenia (6). However, the clinical benefits of corticotherapy are often accompanied by significant limitations such as variability in therapeutic response to labeled dosage and concerns for systemic toxicity; for instance, systemic adverse effects were reported in 10-81% of dogs receiving oral corticosteroids for the treatment of atopic dermatitis (4).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, anti‐inflammatory drugs and antibiotics have shown variable therapeutic effects 2,4 . Other treatment strategies include the combination of a glucocorticoid and a nonsteroidal anti‐inflammatory drug; 8 a combination of glucocorticoids, cyclosporine and desensitization, 4 and use of antifungal medications and inhaled steroids 2,53 . In our study, all dogs that received previous symptomatic treatment for respiratory clinical signs failed to show resolution or sustained improvement.…”
Section: Discussionmentioning
confidence: 72%
“…No specific protocols are available for treating the disease, and only a single clinical trial has been reported. 8 In human medicine, CILPR remains a major problem of public health worldwide. 9 Many studies have postulated a relationship between CILPR and gastrointestinal clinical signs such as those related to gastroesophageal reflux disease (GERD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No specific protocols are available for treating the disease, and only a single clinical trial of 6 weeks' duration has been reported. 12 Although chronic idiopathic lymphoplasmacytic rhinitis is not a life-threatening disease, owners are often distraught at the dog's nasal obstruction or the need to clean up nasal discharge or nasal blood frequently in the house. Despite earlier reports in the literature, systemic or topical corticosteroids are seldom effective in controlling clinical signs 12 and actually may worse them.…”
Section: Introductionmentioning
confidence: 99%